2021
DOI: 10.1155/2021/6615273
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anchote (Coccinia abyssinica) and Potato Starch Addition on Colloidal Stability of Pineapple Juice

Abstract: Starch is one of the most important value-added food ingredients used as a thickener in many foods and industrial applications. This research investigated the effect of different concentrations of starch (anchote and potato) addition on the colloidal stability of pineapple juice. The experiment was carried out on a two-factor factorial design arranged in CRD. The first factor (starch type with two levels (anchote and potato)) and the second factor (starch concentration with three levels (1%, 3%, and 5%)) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
2
4
0
Order By: Relevance
“…In our study, there were no statistically significant deviations in the pH values of fruit juices based on hydrocolloid type and concentration. This finding aligns with the report of Tiruneh et al [ 25 ], which concluded that both type and increasing levels of starch had no significant effect on pH.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In our study, there were no statistically significant deviations in the pH values of fruit juices based on hydrocolloid type and concentration. This finding aligns with the report of Tiruneh et al [ 25 ], which concluded that both type and increasing levels of starch had no significant effect on pH.…”
Section: Discussionsupporting
confidence: 93%
“…Remarkably, among the levels, the honey-like peach juice samples with starch experienced a more pronounced decline in viscosity. The findings resonate with those of Tiruneh et al [ 25 ], who reported that viscosities of pineapple juice samples enriched with 1 %, 2 % and 5 % potato and anchote starch registered significant decreases during storage at 4 °C over a 15-day span. The propensity of xanthan gum, guar gum, and starch to exhibit pseudoplastic properties in suspension systems is noteworthy.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, a study was reported in carrot juices in which much less clarification (less relative sediment height) occurred in juices with no added PME enzyme 14 . Furthermore, a study reported that 5% potato starch could maintain the colloidal stability and relative sediment height at 31.17% in pineapple juices during storage 16 …”
Section: Resultsmentioning
confidence: 98%
“…14 Furthermore, a study reported that 5% potato starch could maintain the colloidal stability and relative sediment height at 31.17% in pineapple juices during storage. 16 Viscosity Table 1 represents the viscosity of control and fruit juices treated with lemon PMEI for all three juices. Higher viscosities of fruit juices are due to the presence of pectic materials in the juice.…”
Section: Relative Turbiditymentioning
confidence: 99%